Investigating the impact of process complexity on quality of care in hospital emergency departments. (1st January 2013) - Strawderman, Lesley; Thomas, Laura R.; Babski-Reeves, Kari; Greenwood, Allen
Prior research has acknowledged the effect of complexity on provider and system performance in hospital emergency departments (EDs). This research examined the impact of ED process complexity on hospital quality outcomes. Nine emergency department nurse managers from hospitals in Mississippi, Alabama, and Louisiana were interviewed regarding processes of registration, laboratory testing, medication administration, radiology and discharge. Interview data was coded according to variables in proposed equations for patient-focused, provider-focused, and overall process complexity. Hospital quality was measured using existing process of care, outcome of care and patient satisfaction standards. Results showed a strong negative correlation between process complexity and overall quality, suggesting that hospitals with lower process complexity experience higher quality outcomes. Regression analysis showed that the average number of patient steps in a process and the overall complexity of the registration process were significant predictors of overall quality. Methods of reducing patient steps and registration process complexity are discussed.